Issuing International Sovereign Bonds : Opportunities and Challenges for Sub-Saharan Africa - Mecagni, Mauro (Departmental Papers; Departmental Paper, 2014)
This African Department Paper examines the rise in international sovereign bonds issued by African frontier economies and recommends policies for potential first-time issuers.